2018
DOI: 10.1007/s00276-018-2069-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability of the palmaris longus muscle in human fetuses

Abstract: PurposeThe palmaris longus (PL) muscle is characterized by high-morphological variability. It is clinically important as it is routinely harvested for the reconstruction of other tendons. The study characterizes the morphology of the PL in human fetuses and creates a new classification based on its variations that would relate to the spectrum of morphological variability in adults.MethodsEighty spontaneously aborted human foetuses (44 male, 36 female, 160 upper limbs), aged 18–38 weeks of gestation, were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
(53 reference statements)
1
33
2
Order By: Relevance
“…The presence of the PLM has been studied predominantly through the method of dissection in cadavers or by inspection in living subjects. In our study, the PLM was present in 100% of the dissected cases, unlike Olewnik et al 13 who found that the PLM was present in 62.5% of fetuses. Its proximal and distal insertion is in accordance with what is reported in the anatomy textbooks, 4,14 that is, the proximal insertion is in the medial epicondyle of the humerus and distally in the palmar aponeurosis.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The presence of the PLM has been studied predominantly through the method of dissection in cadavers or by inspection in living subjects. In our study, the PLM was present in 100% of the dissected cases, unlike Olewnik et al 13 who found that the PLM was present in 62.5% of fetuses. Its proximal and distal insertion is in accordance with what is reported in the anatomy textbooks, 4,14 that is, the proximal insertion is in the medial epicondyle of the humerus and distally in the palmar aponeurosis.…”
Section: Discussioncontrasting
confidence: 87%
“…Its proximal and distal insertion is in accordance with what is reported in the anatomy textbooks, 4,14 that is, the proximal insertion is in the medial epicondyle of the humerus and distally in the palmar aponeurosis. Few studies have reported the PLM morphometry in human fetuses, in our study the average length of the PLM and its tendon of fetuses aged from 19.6 to 37.8 weeks of gestation was of 30.36, our results were larger than those found by Olewnik et al 13 who studied 160 limbs of fetuses aged 18 to 38 weeks of gestation which had an average length of 25.9mm, as well as what was found by Kocabiyik et al 15 who studied 44 limbs of fetuses, with an average length of 25.9mm long at 17 to 40 weeks of gestation.…”
Section: Discussioncontrasting
confidence: 84%
“…RNN/130/20/KE). The age of the fetuses was determined on the basis of craniosacral measurements as well as head measurements (Olewnik, Wa sniewska, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The strength of the muscle decreases as you progressively compare the ancestral genera of primates to more derived primate species, supporting claims of phylogenetic regression of the PL through evolution [2], [3]. Subsequently, in the evolutionarily derived human primate, the PL muscle is less developed and is one of the most morphologically variable muscles of the upper limb [4], [5].…”
Section: Introductionmentioning
confidence: 74%